INTERNATIONAL ROUND TABLE DISCUSSION: IS THERE A PLACE FOR ARTIFICIAL INTELLIGENCE IN SAFE PATIENT HANDLING, MOBILITY, AND FALLS MANAGEMENT? - FRAY, MICHAEL; ROHNER, SVEN; THOMAS, DAVID (International Journal of Safe Patient Handling & Mobility (SPHM), 2023)
INTRODUCTION There has been a lot of discussion in the general media recently on the use of artificial intelligence (AI). Its insidious introduction in our world has rapidly picked up speed. We are now having discussions about how safe it is, whether this is the time to regulate it, how it can be used for good, and what its potential to do harm could be. As AI is gradually integrated into so many daily activities and programs such as ChatGPT are already starting to replace much of the work being done by those who make a living using the written word, the question about whether AI has a place in safe patient handling, mobility, and falls management has been asked in this discussion. Experts from Switzerland, New Zealand and the UK offer their thoughts and opinions on what seems like an inevitable change in society now and in the future.